2019
DOI: 10.3390/ijms20143600
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Adenosine A2A-Dopamine D2 Receptor Heteromers in Parkinson’s Disease Post-Mortem Brain through a New AlphaScreen-Based Assay

Abstract: Background: Several biophysical techniques have been successfully implemented to detect G protein-coupled receptors (GPCRs) heteromerization. Although these approaches have made it possible to ascertain the presence of GPCR heteromers in animal models of disease, no success has been accomplished in pathological human post-mortem brains. The AlphaScreen technology has been consistently used to quantify small analyte accumulation or depletion, bimolecular interactions, and post-translational modifications. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Importantly, the density of each individual D 2 R containing oligomer may be altered in disease conditions, which may constitute a putative pathological fingerprint. Precisely, we recently reported that D 2 R/A 2A R heteromers would be increased in the caudate from human postmortem PD patients (Fernandez-Duenas et al, 2019). This fact would negatively affect dopaminergic neurotransmission, thus providing the rationale for using A 2A R antagonists in PD (see above).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Importantly, the density of each individual D 2 R containing oligomer may be altered in disease conditions, which may constitute a putative pathological fingerprint. Precisely, we recently reported that D 2 R/A 2A R heteromers would be increased in the caudate from human postmortem PD patients (Fernandez-Duenas et al, 2019). This fact would negatively affect dopaminergic neurotransmission, thus providing the rationale for using A 2A R antagonists in PD (see above).…”
Section: Discussionmentioning
confidence: 94%
“…The AlphaLISA R immunoassay was performed as previously described (Fernandez-Duenas et al, 2019). Briefly, WT and D 2 R KO animals were euthanized by cervical dislocation, followed by dissection of striata on an ice-cold plate.…”
Section: Alphalisa R Immunoassaymentioning
confidence: 99%
See 2 more Smart Citations
“…Borroto-Escuela et al present further evidence that A 2A R-D 2 R heteromers in the nucleus accumbens, through A 2A R mediated allosteric inhibition of the D 2 R, can increase anti-reward in the ventral striatopallidal GABA neurons and inhibit cocaine self-administration, whereas the A 2A R homodimer does not appear to be involved in this allosteric mechanism [19]. Subsequently, Fernández-Dueñas et al describe the development of a new AlphaScreen assay to detect GPCR oligomers in post-mortem human brains, thus confirming for the first time the existence of A 2A R/D 2 R heteromers in human caudate [20]. In brief, antibodies against A 2A R and D 2 R were selectively labelled with donor and acceptor beads to engage in a singlet oxygen energy transfer, dependent on the formation of A 2A R/D 2 R heteromers.…”
mentioning
confidence: 95%